2012
DOI: 10.1590/s0102-695x2012005000026
|View full text |Cite
|
Sign up to set email alerts
|

The combined action of phytolarvicides for the control of dengue fever vector, Aedes aegypti

Abstract: Amongst other botanical sources, Annona muricata L., Annonaceae, seeds and Piper nigrum L., Piperaceae, fruits are particularly enriched with acetogenins and piperine-related amides, respectively. These crude ethanolic extracts are potent bioactives that can kill Aedes aegypti larvae (dengue fever mosquito). A. muricata displayed a 93.48 μg/mL LC50 and P. nigrum an 1.84 μg/mL LC50. An uncommon pharmacognostical/toxicological approach was used, namely different combinations of both extracts to achieve an improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Alkaloids were not found in AmSO or AmPtO (data not shown). The principal spot was present in all the samples analyzed in the present study, mainly in the methanol fraction, and may be associated to the presence of annonacin, considering that acetogenin is the major compound in A. muricata seeds (Moghadamtousi et al, 2015;Grzybowski et al, 2012;Champy et al, 2002). The strong absorption at 1745 cm −1 (lactone C=O), a strong aliphatic C-H absorption below 3000 cm −1 in the IR spectrum suggested the presence of an unsaturated lactone moiety in an annonacin-type acetogenin (Champy et al, 2002).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Alkaloids were not found in AmSO or AmPtO (data not shown). The principal spot was present in all the samples analyzed in the present study, mainly in the methanol fraction, and may be associated to the presence of annonacin, considering that acetogenin is the major compound in A. muricata seeds (Moghadamtousi et al, 2015;Grzybowski et al, 2012;Champy et al, 2002). The strong absorption at 1745 cm −1 (lactone C=O), a strong aliphatic C-H absorption below 3000 cm −1 in the IR spectrum suggested the presence of an unsaturated lactone moiety in an annonacin-type acetogenin (Champy et al, 2002).…”
Section: Discussionmentioning
confidence: 53%
“…The thin layer chromatographic profiles were made with AmSO, AmPtO and their fractions obtained by SPE extraction according to Grzybowski et al, (2012). Chromatoplates were made with hexane: chloroform: nitroethane: ethyl acetate: acetone: methanol: acetonitrile: water (12:2:4:4:1:2:1.6:0.1, v/v) as mobile phase.…”
Section: Physiochemical Screening Of Crude Oilmentioning
confidence: 99%
“…The black pepper (P. nigrum L.) is a perennial woody vine species largely traded worlwide as condiment, medicinal purposes, and other uses such as as phytolarvicides in control of dengue insect (Aedes aegypti) (Simas et al, 2007;Grzybowski et al, 2012). Despite the high number of catalogued varieties (around 51) by Mathew et al (2001) in India, in Brazil, the production relies on the Bragantina variety, mainly in pepper nurseries of northern Espírito Santo state.…”
Section: Introductionmentioning
confidence: 99%
“…nigrum extract combination at 9:1. The authors suggest that the synergism of this combination was responsible for the morphological effects that took place in the larvae's bodies that lead to their mortality (Grzybowski et al 2012). Simas et al (2007) reported on the fractionation of P. nigrum ethanol extract.…”
Section: Larvicidal Properties Of Crude Extracts and Sub-fractions Ofmentioning
confidence: 99%